(untitled) (IAHS Medical Journal, 2024)
Background: This study addresses the imperative role of maternal personal and household hygiene in safeguarding young children from diarrhea in rural Bangladesh. With young children facing heightened susceptibility to diarrhea during weaning, potential sources of contamination include traditional weaning foods, water quality, and utensil hygiene. This study aims to investigate the influence of maternal hygiene practices on the prevalence of diarrhea among young children in rural area of Khulna, Bangladesh. Materials and methods: A cross-sectional study was conducted in rural areas of Bangladesh from January to June 2023, focusing on under-five children and their working mothers. Results: The study revealed significant associations between hygiene practices and diarrhea prevalence. Proper hand washing by mothers before food preparation exhibited a protective effect (OR: 1.83, 95% CI: 1.03 - 3.24). Ensuring utensil hygiene was correlated with lower diarrhea risk (OR: 11.29, 95% CI: 5.19 - 24.55). Moreover, consistent maternal hand washing after using the toilet (OR: 6.92, 95% CI: 3.08 - 15.55) and before feeding (OR:2.38, 95% CI: 1.17 - 4.82) significantly reduced diarrhea risk among children. Conclusion: The study underscores the critical role of maternal personal and household hygiene practices in preventing diarrhea among young children in rural Bangladesh. IAHS Medical Journal Volume 6(2) December 2023; 73-77